Cross comparison of seminal plasma proteins from cattle and buffalo (Bubalus bubalis) - Codognoto, Viviane Maria [UNESP]; Yamada, Paulo Henrique [UNESP]; Schmith, Rúbia Alves [UNESP]; Rydygier de Ruediger, Felipe [UNESP]; de Paula Freitas-Dell’Aqua, Camila [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Brochine, Suzane [UNESP]; do Carmo, Lucas Monteiro [UNESP]; Vieira, Andressa Filaz [UNESP]; Oba, Eunice [UNESP] (Wiley, 2020)
The objective of this study was to evaluate seminal plasma proteins from cattle and buffalo (Bubalus bubalis), to identify differences between related species. Sixteen buffaloes and 16 cattle between 30 and 60 months of age were used. Semen collection was performed by electroejaculation, followed by macroscopic and microscopic subjective analyses. After analysis, the samples were centrifuged at 800 g for 10 min, and the supernatant (seminal plasma) was recentrifuged at 10,000 g for 30 min at 4°C. The total protein concentration was determined by the Bradford method, and the proteins were digested in solution for mass spectrometry (nLC-MS/MS). Multivariate statistical analysis was used to evaluate the proteomics results by non-hierarchical clustering the considering exponentially modified protein abundance index (emPAI). Principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) were used for clustering. Proteomics identified 78 proteins, and multivariate analysis showed 4 that were over-expressed in buffaloes (cystatin C, prosaposin, peptide YY and keratin type II cytoskeletal 5) and 9 in cattle (spermadhesin-1, seminal plasma protein PDC-109, ribonuclease 4, metalloproteinase inhibitor 2, acrosin inhibitor 1, seminal ribonuclease, C-type natriuretic peptide, angiogenin-1 and osteopontin). Among the proteins identified in seminal plasma, the C-type natriuretic peptide and metalloproteinase inhibitors were described for the first time in buffaloes. Some protease inhibitors were found over-expressed in buffaloes, and important proteins in seminal plasma of cattle were not identified or were found at lower expression levels in buffaloes, which can contribute to reproductive performance in this species.
Keywords: male; proteomics; semen; spectrometry-mass